2021
DOI: 10.1111/imm.13388
|View full text |Cite
|
Sign up to set email alerts
|

PD‐1‐induced proliferating T cells exhibit a distinct transcriptional signature

Abstract: Summary Ligation of the inhibitory receptor PD‐1 on T cells results in the inhibition of numerous cellular functions. Despite the overtly inhibitory outcome of PD‐1 signalling, there are additionally a collection of functions that are activated. We have observed that CD4+ T cells stimulated through the T‐cell receptor and PD‐1 primarily do not proliferate; however, there is a population of cells that proliferates more than T‐cell receptor stimulation alone. These highly proliferating cells could potentially be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 56 publications
0
1
0
Order By: Relevance
“…This notion was further supported by studies in which it was observed that following PD-1 ligation, the transcriptional signature of proliferating CD4 + T cells was enrichment in genes associated with an activated state. Furthermore, they observed that the genes induced after PD-1 ligation significantly differed between PD-L1 and PD-L2 stimulation [155,156]. These observations are consistent with the idea that PD-1 may be involved in regulating specific cellular functions beyond its inhibitory role.…”
Section: Is It Possible That Pd-1/pd-l1/2 Has Also Another Important ...supporting
confidence: 65%
“…This notion was further supported by studies in which it was observed that following PD-1 ligation, the transcriptional signature of proliferating CD4 + T cells was enrichment in genes associated with an activated state. Furthermore, they observed that the genes induced after PD-1 ligation significantly differed between PD-L1 and PD-L2 stimulation [155,156]. These observations are consistent with the idea that PD-1 may be involved in regulating specific cellular functions beyond its inhibitory role.…”
Section: Is It Possible That Pd-1/pd-l1/2 Has Also Another Important ...supporting
confidence: 65%
“…Ranking PD-L1 PD-L2 PD-L1 PD-L2 PD-L1 PD-L2 (Strazza et al, 2021). With our currently ongoing research, we have demonstrated PD-1's ability to differently affect cell proliferation, maturation, and diverse transcript signatures generated by the same PD-1 in different subsets of cells.…”
Section: Naive CM Emmentioning
confidence: 92%